2008
DOI: 10.1111/j.1365-313x.2008.03454.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization of the mutant protein phosphatase abi1 is required for insensitivity towards ABA responses in Arabidopsis

Abstract: SummaryABI1, a protein phosphatase 2C, is a key component of ABA signal transduction in Arabidopsis that regulates numerous ABA responses, such as stomatal closure, seed germination and inhibition of vegetative growth. The abi1-1 mutation, so far the only characterized dominant allele for ABI1, impairs ABA responsitivity in both seeds and vegetative tissues. The site of action of ABI1 is unknown. We show that there is an essential requirement for nuclear localization of abi1 to confer insensitivity towards ABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 77 publications
4
105
0
Order By: Relevance
“…In a recent report, Moes et al (2008) described the nuclear localization of ABI1 wild-type and mutant proteins and the requirement of a functional nuclear localization sequence in order to regulate ABA sensitivity and ABA-dependent gene expression, and they suggested that ABI1 reprograms sensitivity toward ABA in the nucleus. Similarly, Sáez et al (2008) confirmed the interaction of HAB1 and SWI3B (an Arabidopsis homolog of the yeast SWI3 subunit of SWI/SNF chromatin-remodeling complexes) in the nucleus and suggested a direct involvement of HAB1 in the regulation of ABA-induced transcription.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report, Moes et al (2008) described the nuclear localization of ABI1 wild-type and mutant proteins and the requirement of a functional nuclear localization sequence in order to regulate ABA sensitivity and ABA-dependent gene expression, and they suggested that ABI1 reprograms sensitivity toward ABA in the nucleus. Similarly, Sáez et al (2008) confirmed the interaction of HAB1 and SWI3B (an Arabidopsis homolog of the yeast SWI3 subunit of SWI/SNF chromatin-remodeling complexes) in the nucleus and suggested a direct involvement of HAB1 in the regulation of ABA-induced transcription.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, gene products of At1g07430, AtPP2CA/AHG3, and ABI1 have NLS in the C terminus of the PP2C domain, while ABI2, HAB1, and HAB2 gene products do not have obvious NLS. The role of nuclear localization of group A PP2Cs is not clearly understood, but, recently, it has been shown that the basic amino acid cluster found in the C terminus of ABI1 directs nuclear localization when the abi1-1 mutation has been introduced, suggesting that its nuclear localization is responsible for causing a hypermorphic phenotype (Moes et al, 2008). The mode of regulation of MpABI1 by NLS in the N-terminal domain would be different from that of ABI1 with C-terminal NLS.…”
Section: Roles Of the N-terminal Domain Of Mpabi1mentioning
confidence: 99%
“…Arabidopsis protoplasts of the ABA-deficient aba2-1 mutant (10 5 protoplasts in 0.1 mL) were transfected with 5 μg DNA of reporter construct (pRD29B::LUC), 3 μg of p35S::GUS plasmid as a control for internal normalization of expression, and various levels of effector expression cassettes as indicated. The effector cassettes drive expression of RCAR and PP2C cDNA under control of the 35S promoter (20), and all constructs were verified by DNA sequence analysis. The total amount of transfected DNA per assay remained constant by supplementation with DNA of the empty effector cassette.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation and analysis of Arabidopsis protoplasts were performed as described (20). Arabidopsis protoplasts of the ABA-deficient aba2-1 mutant (10 5 protoplasts in 0.1 mL) were transfected with 5 μg DNA of reporter construct (pRD29B::LUC), 3 μg of p35S::GUS plasmid as a control for internal normalization of expression, and various levels of effector expression cassettes as indicated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation